Investigating translation strategies in Indonesian best seller novel (Englisia : Journal of Language, Education, and Humanities, 2022)
Translation strategies have been the subject of extensive investigation. Most people believe that translators use specific strategies and that basic translation strategies are sometimes insufficient. As a result, numerous scholars have investigated and analyzed various translation techniques from various perspectives. This study determined the translation strategies in the novel of Negeri 5 Menara and its English Version, The Land of Five Towers using Baker's (2011) framework. This study was conducted using a descriptive qualitative technique to determine the translation strategies in Negeri 5 Menara and its English version, The Land of Five Towers. There were 130 data points in all. According to the findings, 11% about the use of the more general word, 14 % in the use of the more neutral or expensive word, 8% of cultural substitution, 5% of loan words, 4% of omission, paraphrase with related terms accounted for 57% of all translation tactics, while paraphrasing with unrelated words accounted for 2%, and there was no data on illustration. There were 21 uncategorized data points for every given strategy. It was predicted that in the future, a translator, who is also a pre-service teacher, should widen his or her translation methodologies in order to combat non-equivalence translation.
Keywords: Translation